Persepsi Orang Tua terhadap Konsep Bermain Anak di Tadika Ilmu Hayati di Kuala Lipis, Pahang Malaysia - Hafizah, Nor Amirah; Ismet, Syahrul (Asian Journal of Early Childhood and Elementary Education, 2024)
This research was motivated by the problem of parents not understanding the concept of playing for children aged 5-6 years at Tadika Ilmu Hayat, Kuala Lipis, Pahang, Malaysia. This is because there are many influencing factors, including the job held by parents which can also influence their views on the concept of play for children at school. The aim of this research is to find out the views of preschool parents and to describe differences in parents' views regarding the concept of children's play at Tadika Ilmu Hayat, Kuala Lipis, Pahang, Malaysia.This type of research is quantitative research with data analysis techniques through service studies. The population in this research was 40 people, consisting of 20 mothers and 20 fathers as the research sample. This research instrument used a questionnaire, so that a sample size of 40 people was obtained. The data collection tool is a questionnaire with a Likert Scale model which has been tested for validity and reliability using the SPSS (Statistical Package and Social Science) 20.0 For Windows program.The research results show that: (1) General Perception of Children's Games is 86%; (2) Parents' perception of the concept of playing at home was 75.75%; (3) Parents' perception of the concept of play in preschool is 83.75%.Based on the results of research data analysis, it can be concluded that the hypothesis can be accepted empirically. This means that it is clear that the mother's percentage is higher than the father's. This has proven that mothers play a more important role in responding to children's play concepts than fathers. Apart from that, the mother's response is higher than the father's because the mother spends more time with the child than the father.